Sổ tay hướng dẫn quản lý rơm rạ theo hướng nông nghiệp tuần hoàn và phát thải thấp ở đồng bằng sông Cửu Long - Nguyen Van Hung; Nguyen Van Vuong; Tran Ngoc Thach; Duong Nguyen Khang; Pham Van Thuyet; Tran Thi Cam Nhung; Nguyen Van Hieu; Nguyen Thanh Nghi; Pham Thi Minh Hieu; Tran Thi My Hanh; Tran Thai Nghiem; Le Vinh Thuc; et al. (Ministry of Agriculture and Rural Development, 2023)
The document “Technical manual: Rice straw management towards circular economy and low emission in the Mekong Delta” introduces readers to the characteristics of rice straw, the current status of its treatment, and the management process for using rice straw in a circular way to reduce GHG emissions in rice production. This manual will be a handbook for farmers, extension officers, cooperatives, and others who are interested in rice production that is associated with circular greenhouse gas emission reduction.